Tantangan Guru PAI Dalam Meningkatkan Akhlak Siswa Di Era Revolusi Industri 4.0 di SMP Islam Muallimin Kepung Kediri - Dewi Wulan Sari; Fatkhulloh Abdul Malik; Mohammad Saat Ibnu Waqfin (JoEMS (Journal of Education and Management Studies), 2022)
This research uses descriptive research, namely research that seeks to describe a symptom, an event, an event that is happening now. Through descriptive research, the researcher tries to describe the events and incidents that are the center of attention without giving special treatment to these events. Data collection was done by observing, interviews and documentation. The results of this study indicate that : 1) There is a challenge for Islamic Education teachers in improving the morals of students. 2) Supporting factors of optimizing Islamic Education learning and inhibiting factors from optimizing islamic education learning. 3) and the last of the results of this study is the solution to the problems faced by islamic education teachers regarding the challenges of improving students morals, namely by improving the quality of themselves for teachers both in terms of teaching and in matters relating to teacher personality. Improve teacher professionalism by participating in programs related to teacher competence.